La crítica a la noción tradicional de verdad en Ser y Tiempo. - Carrió, Sara Escobar (Humanidades: Revista de la Universidad de Montevideo, 2005)
In this article, an analysis is made of the criticism of the traditional concept of truth, as expressed by Heidegger in Being and Time, based on ideas originating in the courses he taught in Freiburg and Marburg. An attempt is also made to reveal the part that Heidegger’s characteristic interpretation of Aristotle’s practical philosophy plays in the source of this rejection of truth as an adaptation performed by judgment and the development of a concept of truth as an unveiling which takes place within the context of a wider relationship between Dasein andthe world.